Ideology and Disengagement: A Case Study of Nationalists and Islamists in Chechnya. Issue 2 (7th February 2020) - Souleimanov, Emil Aslan; Aliyev, Huseyn
Abstract: Disengagement from militant groups has often been explained in individual terms such as battle fatigue or the desire to rejoin family and friends. We seek to examine empirically which other factors, beyond individual-level determinants, have influenced disengagement processes among militants belonging to different types of Chechen militant organisations. Drawing empirical insights from unique in-depth interviews with former members of the Chechen insurgency, their relatives, eyewitnesses to the Chechen wars and experts with first-hand knowledge of the researched phenomena, this study examines disengagement among jihadist and nationalist Chechen militants. Focusing on group-level factors, such as the capacity to resist external pressures, the use of violence, in-group social bonds and group cohesion, this article demonstrates that disengagement has been a less viable course of action for Chechen jihadists than for nationalist militants.